2012
DOI: 10.1080/1406099x.2012.10840519
|View full text |Cite
|
Sign up to set email alerts
|

FDI in the post-EU accession Baltic Sea Region: A global or a regional concern?

Abstract: This paper investigates the dynamics of FDIs in the Baltic Sea Region (BSR) by applying the Poisson Pseudo-Maximum Likelihood estimation method on a gravity model. In particular, we analyze the influence of macro and spatial factors on investment stock changes and discuss whether the origin of these investments and the 2004 EU enlargement have had any effects on BSR FDIs.Our results suggest that EU enlargement has been significant for FDI activity in the region, and that FDI is basically a regional issue as it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Building on previous literature that has considered the role of the EU integration process in institutional development and thereby FDI attraction, (Oxelheim and Ghauri, 2004;Nakamura et al 2012), we consider data in the World Governance Index (WGI) in 16 Eastern European countries 2 . These include countries that are on their way to EU membership, current members and non-members.…”
Section: Methodsmentioning
confidence: 99%
“…Building on previous literature that has considered the role of the EU integration process in institutional development and thereby FDI attraction, (Oxelheim and Ghauri, 2004;Nakamura et al 2012), we consider data in the World Governance Index (WGI) in 16 Eastern European countries 2 . These include countries that are on their way to EU membership, current members and non-members.…”
Section: Methodsmentioning
confidence: 99%
“…FDI can be researched in two ways as inflows and outflows as well as outward and inward stocks. We selected stock inward data, in order to reduce missing data due to minus flows logarithm, and this solution is also widely applied in various empirical research [Nakamura, Olsson, Lönnborg 2012]. Subasat and Bellos [Subasat, Bellos 2013] in their gravity model analysis "use FDI stocks because stocks are more stable than flows" as they underline.…”
Section: Methodsmentioning
confidence: 99%
“…(2004) and Medve‐Bálint (2014) held that the EU’s expansion was one of the important reasons for the rapid growth of FDI stock in CEE over the past 10 years. Richard Nakmura et al (2012) used the Poisson pseudo maximum likelihood estimation method to test the impact of the EU’s accession on the FDI stock in the Baltic Sea region, and the results revealed that the average level of FDI stock in this region increased by 6% after the EU’s accession compared with before. The results achieved by Jones et al (2017) showed that the EU’s enlargement reduced border costs, and in turn, strengthened the attractiveness of FDI.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%